Correlation of Authoritative Parenting Style and Discipline of Study Toward Students’ Mathematics Knowledge Competence - Setiawan, Dewa Putu Reza (International Journal of Elementary Education, 2020)
Some factors give an impact on the student in elementary school. The discipline of studying and parenting style from the parents. Some of the parents are not realizing that parenting style will give an impact on the study result of their children. This research is aimed to determine the effect of the authoritative parenting style and discipline of studying to the competence of student mathematical knowledge. The type of research that is used is ex-post facto research with correlational research design. The population that used in this research is the fifth-grade students of the State Elementary School Group I Gusti Ngurah Jelantik, amounted to 178 students. The sample is determined by a proportional random sampling technique. The result of multiple regression analysis found the equation Ŷ = 8.205 + 0.958X1 + 0.358X2, and result Freg = 84.209 > Ftable = 3.075. The Coefficient of determination (R2) = 0.594. Thus, meant score Freg is significant.  Based on the result of the research, it can be concluded that there is a significant influence between the authoritative parenting style and discipline of studying to the competence of student mathematical knowledge of fifth-grade students with the percentage of influence about 59.4%.